Management of benign anastomotic strictures following rectal resection: a systematic review. (13th September 2021) - Clifford, Rachael Elizabeth; Fowler, Hayley; Manu, Nicola; Vimalachandran, Dale
Abstract: Aim: Benign anastomotic strictures following colorectal surgical resection are a commonly under‐reported complication in up to 30% of patients, with a significant impact upon quality of life. In this systematic review, we aim to assess the utility of endoscopic techniques in avoiding the need for surgical reintervention. Method: A literature search was performed for published full text articles using the PubMed, Cochrane and Scopus databases. Additional papers were found by scanning the references of relevant papers. Results: A total of 34 papers were included, focusing upon balloon dilatation, endoscopic stenting, electroincision, stapler stricturoplasty and cortiocosteroids alone and in combination, with success rates varying from 20% to 100%. The most challenging strictures were reported as those with a narrow lumen, frequently observed following neoadjuvant chemoradiotherapy or an anastomotic leak. Endoscopic balloon dilatation was the most commonly used first‐line method; however, repeated dilatations were often required and this was associated with an increased risk of perforation. Although initial success rates for stents were good, patients often experienced stent migration and local symptoms. Only a small number of patients experienced endoscopic management failure and progressed to surgical intervention. Conclusion: Following identification of an anastomotic stricture and exclusion of underlying malignancy, endoscopic management is both safe and feasible as a first‐line option, even if multiple treatment exposures or multimodal management is required. Surgical resection or a defunctioning stoma should be reserved for emergency or failed cases. Further research is required into multimodal and novel therapies to improve quality of life for these patients.